BIOLOGICAL CONTROL OF BANDED LEAF AND SHEATH BLIGHT DISEASE (Rhizoctonia solani KUHN) IN CORN WITH FORMULATED Bacillus subtilis BR23 - Muis, Amran; Quimio, Arcadio J. (Indonesian Journal of Agricultural Science, 2006)
Rhizoctonia solani Kuhn. causing banded leaf and sheath blightdiseases is one of the important fungi of corn world wide. Thefungus is commonly controlled by using fungicide because noresistant variety available. The objective of the study was todevelop a seed treatment formulation of the selected Bacillussubtilis to control R. solani in corn. The study was conductedin the Department of Plant Pathology, College of Agriculture,University of the Philippines Los BaÃ±Ã²s, College, Laguna fromMay 2004 to August 2005, using sweet corn var. IPB Supersweetas test plant. Corn seeds were surface sterilized for 10 minutesin 1% sodium hypochlorite solution and 5% ethanol, washedthrice with sterile distilled water and air-dried. The seeds werecoated with formulated B. subtilis BR23 and used for severalexperiments, such as evaluation for their germination andgrowth in the laboratory, effectively on R. solani in the bakedand nonbaked field soil under greenhouse condition, and in themicroplots artificially infested with R. solani. The treatmentwas compared with other standard seed treatment of syntheticfungicides such as captan (10 g per kg seeds) and metalaxyl (10g per kg seeds). The experiments were designed in a completelyrandom design with three replications. Parameters observedwere seed germination, plant height, disease scores, and plantyield. Laboratory formulated B. subtilis BR23 used as seed treatmenthad no detrimental effects on seed germination andseedling vigor. In microplots artificially infested with a selectedhighly virulent R. solani, seed treatment with the same formulationincreased grain yield by 27% compared to that of thecontrol captan seed treatment with 14.4%. The studies showedthe potential of B. subtilis BR23 for commercialization as aseed treatment for the control of banded leaf and sheath blightdisease (R. solani) in corn.